The relationship between family and lifeworld in the context of Edmund Husserl´s phenomenological approach - Rynkiewicz, Kazimierz (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
The essay seeks to phenomenologically outline the relationship between the family and the lifeworld. By referring to Husserl, the fundamental perspective of the analysis is formulated. It follows that there are two types of phenomenological components to consider: pre-scientific and scientific. Then different family patterns can be developed. In this process, the thesis The „acceptance of oneself” is very important. The ontic reinforcement of responsibility must not be neglected in the area of the social.